Climatological influence of land and atmospheric initial conditions on North America and Eurasia surface temperature and circulation in the past 57 years (1958–2014) reforecasts - Ravi P Shukla (Environmental Research Letters, 2020)
This study demonstrates the potential impact of land and atmospheric initial conditions (ICs) on the mean state of land surface temperature (SKT) and mid-troposphere circulation over Eurasia and North America (NA) using the Climate Forecast System version-2 (CFSv2) ensemble seasonal reforecasts for 1958–2014. The land ICs and atmosphere ICs have assembled from several different data sources before and after 1979 in January initialized reforecasts (JIR). Therefore, two-time periods have defined, earlier period (1958–1978) and later period (1994–2014). The climatological difference between JIR P58-78 and P94-14 depicts enhanced cold SKT and sub-surface temperature at 0–10 cm over northern Eurasia and northeast region of NA from May to June. Model overestimates snow cover fraction from May to June in JIR P58-78 than JIR P94-14, which leads to excessive upwards-shortwave radiation in the northern latitudes. Due to cold temperature from the surface to mid-troposphere, model depicts lower geopotential heights in mid-troposphere, which leads to increase westerly winds at mid-troposphere over northern latitudes from May to June. The climatological differences between earlier and later periods of JIR from May to June are similar to differences between reforecasts initialized in winter and spring as reported by some recent studies. The climatological difference between JIR P58-78 and P94-14 depicts enhanced cooling from surface to 600 hPa over northern latitudes in January. As lead months increase, the magnitude of cold temperature decreases gradually from February to March. Most prominent centers of geopotential height from surface to mid-troposphere over northern latitude in climatological differences between earlier and later periods of JIR in January vanish in February. The different sources of ICs and the nature of land conditions before and after 1979 are main causes of large differences in JIR from May to June over northern latitudes.